2017
DOI: 10.1002/jso.24599
|View full text |Cite
|
Sign up to set email alerts
|

Local recurrence after laparoscopic radiofrequency ablation of malignant liver tumors: Results of a contemporary series

Abstract: This study shows that 14% of malignant liver tumors will develop LR within a year after LRFA. Additional 4% of the lesions will demonstrate recurrence within 1 cm of the ablation zone, mostly as part of a multifocal recurrence. Ablation margin is the only parameter that the surgeon can manipulate to decrease LR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 21 publications
(43 reference statements)
8
34
1
1
Order By: Relevance
“…Local recurrence by tumor type (n, total number, %) obtained with RFA, which was 18.4% in our most recent experience. 18 Although these numbers are in line with the results of other recent MWA studies in the literature, [11][12][13][14] it is important to understand the parameters that affect the outcome of liver tumor ablation.…”
Section: Definite Suspicious Overallsupporting
confidence: 73%
See 1 more Smart Citation
“…Local recurrence by tumor type (n, total number, %) obtained with RFA, which was 18.4% in our most recent experience. 18 Although these numbers are in line with the results of other recent MWA studies in the literature, [11][12][13][14] it is important to understand the parameters that affect the outcome of liver tumor ablation.…”
Section: Definite Suspicious Overallsupporting
confidence: 73%
“…Although it is impossible to know if the latter is an LR or not, we have consistently reported these as LR in previous publications. 15,[17][18][19] When these are accounted as well, it is seen that 82% of the LRs reported in this study were true LRs and 18% suspicious.…”
Section: Definite Suspicious Overallmentioning
confidence: 68%
“…After analyzing and comparing the DSA, we concluded that the blood supply characteristics of the metastatic tumor in the same liver were not identical and that a portion of the CRCLM patients would be resistant to chemotherapy, so not every lesion can be controlled well by TACE alone. To achieve a better control of liver metastases, local ablation combined with RFA and CRA is frequently used in our department, and the effectiveness and safety of RFA has been confirmed by some researchers [33,34]. In addition, the use of RFA or CRA is limited in lesions near major bile ducts and great vessels; therefore, the combination of two or more minimally invasive interventional methods to complement the other's advantages may be a necessary strategy.…”
Section: Discussionmentioning
confidence: 98%
“…Real-time ablation monitoring is necessary to improve the efficiency of the treatment and avoid unwanted risks 2 . While the temperature of the needle probe and tissue impedance monitoring could be of some help in this regard, there exists a need for more accurate ablation monitoring to improve treatment efficiency and to reduce the tumor recurrence 2,3 .…”
Section: Introductionmentioning
confidence: 99%